Complete Intraventricular Migration of Ventriculoperitoneal Shunt: Once in a Blue Moon Phenomenon of Shunt Surgery - Yadav, Vikrant; Prasad, Ravi Shankar (Indian Journal of Neurosurgery, 2023)
Shunt surgery is a very common neurosurgical procedure for hydrocephalus. It is associated with numerous complications, and intraventricular shunt migration is one of rarest. Various mechanisms have been described to explain this rare entity. Hereby we present an index case of this rare complication of shunt surgery in which patient presented with tuberculous meningitis with hydrocephalus having intraventricular shunt migration and will discuss possible mechanisms responsible for it. A 1-year old male infant, previously diagnosed case of tuberculous meningitis with hydrocephalus with right-sided ventriculoperitoneal shunt in situ, presented to the emergency department with bulging fontanelles secondary to shunt malfunction. Left-sided ventriculoperitoneal shunt was inserted. After few months, patient turned up again with left-sided shunt malfunction and right-sided intraventricular migrated shunt. Endoscopy-assisted removal of intraventricular migrated shunt and simultaneous third ventriculostomy was done. Patient improved in postoperative period. Being an extremely uncommon complication, intraventricular migration of shunt described as “once in a blue moon” phenomenon. It can be avoided by proper surgical technique with adequate-sized burr hole. Removal of shunt is preferred for prevention of infection.
Keywords: hydrocephalus; ventriculoperitoneal shunt; intraventricular migration